Thrombin Generation Decrease After LMWH Administration in an Antithrombin-Deficient Pregnant Woman With a Homozygous HBS II Mutation - Malikova, Ivana; Husakova, Martina; Bilkova, Jana; Brzezkova, Radka; Hrachovinova, Ingrid; Kvasnicka, Tomas (Clinical and applied thrombosis/hemostasis, 2023)
The cases of antithrombin (AT)-deficient pregnant women with a homozygous HBS II mutation are relatively rare and are accompanied by an increased thrombophilic risk, which is manifested by increased thrombin generation (TG). It is very difficult to ensure their prophylactic treatment during pregnancy. We aimed to determine the utility of the thrombin generation assay (TGA) and anti-factor Xa (anti-FXa) test to monitor the effects of a prophylactic dose of low-molecular-weight heparin (LMWH) in a 28-year-old woman with homozygous AT deficiency caused by mutation c.391C > T#, (p.Leu131Phe†) in the SERPINC1 gene and to compare the findings with those from a group of pregnant and non-pregnant women also treated with LMWH. TG monitoring was chosen due to severe AT deficiency that was manifested by low levels of anti-FXa activity when monitoring the efficacy of LMWH treatment. A significant decrease in TG was detected in all monitored groups (P < .05). There were no thrombotic complications during the whole pregnancy of the woman with AT deficiency. Consistent monitoring of TG with LMWH anticoagulant therapy administration during pregnancy together with AT administration before and after delivery may improve the overall condition of pregnant women and the quality of their care.
Keywords: homozygous mutation; thrombin generation; Antithrombin III Deficiency; těhotenství; antithrombin III; mutace; antithrombin deficiency; Adult; Thrombin; Antithrombins; nedostatek antitrombinu III; antitrombiny; trombin; antikoagulancia; ženské pohlaví; Mutation; těhotné ženy; Humans; Anticoagulants; Pregnancy; Antithrombin III; Pregnant People; LMWH administration; Heparin, Low-Molecular-Weight; dospělí; Female; heparin nízkomolekulární; lidé